Predictors of therapy switching to high-efficacy disease-modifying therapies in patients with multiple sclerosis: a single center, retrospective, observational study - Makarevičius, Gytis; Kizlaitienė, Rasa; Kaubrys, Gintaras; Giedraitienė, Nataša (Frontiers in Neurology, 2025)
ObjectThe treatment of multiple sclerosis (MS) with high-efficacy disease-modifying therapies (HE-DMTs) may lead to better long-term outcomes for patients. There is an ongoing debate about which patients should initially start with these treatments. The objective of this study was to assess the first symptoms at the time of MS diagnosis and to identify independent predictors of treatment switching to HE-DMTs in MS patients within 5 years after diagnosis.Materials and methodsA single-center retrospective, observational study was conducted at tertiary MS center Vilnius University Hospital Santaros Klinikos, Lithuania. 319 patients newly diagnosed with relapsing MS who were initially treated with MS platform therapy between 2010 and 2019 were included.ResultsDuring the disease course, 26.65% of patients were switched from platform therapy to HE-DMTs within 5 years of follow-up. Factors associated with the need to switch therapies were younger age (p < 0.001), shorter disease duration (p < 0.001) and higher progression index (p < 0.001) at diagnosis, lower initial EDSS (p = 0.003) and the presence of cerebellum and/or brainstem symptoms (p = 0.047). Younger age, shorter disease duration and cerebellar/brainstem presentation at diagnosis remained statistically significant after logistic regression analysis.ConclusionYounger age, shorter disease duration and cerebellar/brainstem presentation at diagnosis were consistently associated with the need to escalate platform.